Energy Policy Options for Sustainable Development in Bangladesh - Herath Gunatilake; David Roland-Holst (Asian Development Bank (ADB), 2013)
Bangladesh today faces a different future than it did decades ago when relatively abundant natural gas seemed to be the key to prosperity. To support more evidence-based dialogue on energy development, allocation, and pricing reform, this study uses a computable general equilibrium model to evaluate major energy policy issues facing Bangladesh. A relatively small negative growth impact of increased energy prices can be easily counteracted by an economy-wide increase in energy efficiency or subsidized gas for fertilizer production. A gas price increase does not lead to significant inflationary pressures in the country's economy. Diversification of the power sector fuel mix by introducing coal provides good macroeconomic indicators but results in higher carbon emissions. Investing the gas revenue in physical and social infrastructure provides the best macroeconomic indicators. This best policy option, however, further increases carbon emissions. Impacts of these different policies in terms of increased household income are more or less equally distributed among different household groups. Most of the attractive policy options have the drawback of higher carbon emissions, and supplementary policies and suitable technology adoption should play a balancing role.
hdl:11540/2292
Keywords: Q32; Q43; 330; energy policy; gas pricing reforms; general equilibrium models; Bangladesh